OS03.7.A Clinical characteristics, treatment and long-term outcome of patients with brain metastases from thyroid cancer - an analysis of the Vienna Brain Metastasis Registry. (5th September 2022) - Wolff, L; Steindl, A; Dieckmann, K; Gatterbauer, B; Widhalm, G; Berghoff, A; Preusser, M; Raderer, M; Kiesewetter, B
Abstract: Background: The incidence of brain metastases (BM) in patients with thyroid cancer (TC) depends on the histological subtype. About 1% of patients with differentiated (DTC), 3% with medullary (MTC) and up to 10% with anaplastic thyroid cancer (ATC) develop BM. The diagnosis of BM drastically worsens the prognosis of TC. Given the rare incidence, little is known about the presentation and outcome of this cohort. Material and Methods: Patients with a histologically verified diagnosis of TC and BM were identified from the Vienna Brain Metastasis Registry, a comprehensive database managed by the Division of Oncology, Medical University of Vienna, including patients with cerebral metastasis since 1990. Data were obtained from medical records comprising clinicopathological features, treatment, BM-specific characteristics and outcome. Results: 20/6074 patients included in the registry had a diagnosis of TC and radiologically verified BM. 13/20 (65%) were female and the median age at diagnosis of TC and manifestation of BM was 56 years (range 21-75) and 68 years (range 45-75), respectively. In terms of histology, 18/20 (90%) had DTC, one MTC and one ATC. Interestingly, 10/18 DTC presented with follicular histology which underlines the more aggressive course of this rare subtype. 6/20 (30%) had BM at primary diagnosis (DTC n=5, ATC n=1), while the remaining developed BM during follow-up. The median time to diagnosis of BM was 2.6 years for DTC (range 0-42), 22 years in the MTC patient and 2 months for ATC. Regarding BM-specific characteristics, all but one patient had symptoms due to BM (neurological deficits n=11, increased intracranial pressure n=5, seizures n=3). Most patients (13/20) had a singular BM, commonly located in the left hemisphere (8/13), and only one had more than three BMs. Upfront treatment for BM was local therapy (resection n=9, stereotactic radiosurgery n=7, whole brain radiotherapy n=3); one patient received supportive care only. The median overall survival (mOS) from diagnosis of TC was 6 years for DTC (range 2.5 months-42 years), 33 years for the MTC and 9 months for the ATC. The mOS from diagnosis of BM was 14 months for DTC (1.8 months-16 years), 22 years for the MTC and 3 months for the ATC. Conclusion: Few patients with TC develop BM, which present commonly as single lesion. While in general BM constitute a poor prognostic factor, individual patients experience long-term survival following local therapy. More information about the optimal management of BM in TC is needed to enable guideline recommendations.